(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This empirical study examines the long-run and short-run relationship between financial inclusion and economic growth in seven Association of Southeast Asian Nations (ASEAN) countries including Indonesia, Malaysia, the Philippines, Thailand, Vietnam, Cambodia, and Lao PDR. Using Pooled Mean Group Autoregressive Distributed Lag (PMG-ARDL) model, the analysis regresses three financial inclusion determinants namely number of commercial bank branches, account ownership, and automated teller machines (ATM) against the GDP per capita, the proxy of economic growth, with a designated set of control variables. The panel data covers the period of 2000 to 2021. The findings contribute to the literature on the subject by providing empirical evidence of a positive and statistically significant long-run relationship between financial inclusion determinants and GDP per capita in the ASEAN region. The study’s findings indicate that, in a long run, a 1% increase in commercial bank numbers corresponds to a 0.57 % increase in GDP growth, while a 1% increase in number of account ownership is linked to a 1.03 % increase in GDP growth. However, evident of the effects of numbers of ATM is less significant, although a 1% increase of this variable is associated with a 0.23 % rise in GDP growth. The short-run relationship between financial inclusion and economic growth is mixed and varies across different estimation lags, highlighting the complexity of the relationship. The study offers important policy implications for ASEAN economies and beyond, suggesting that policymakers in the region need to continue promoting financial inclusion for long-run positive effects on economic growth.